Genome and Phylogenetic Analysis of Genes Involved in the Immune System of Solea senegalensis – Potential Applications in Aquaculture - García-Angulo, Aglaya; Merlo, Manuel A.; Rodríguez, María E.; Portela-Bens, Silvia; Liehr, Thomas; Rebordinos, Laureana (Frontiers in Genetics, 2019)
Global aquaculture production continues to increase rapidly. One of the most important species of marine fish currently cultivated in Southern Europe is Solea senegalensis, reaching more than 300 Tn in 2017. In the present work, 14 Bacterial Artificial Chromosome (BAC) clones containing candidate genes involved in the immune system (b2m, il10, tlr3, tap1, tnfα, tlr8, trim25, lysg, irf5, hmgb2, calr, trim16, and mx), were examined and compared with other species using multicolor Fluorescence in situ Hybridization (mFISH), massive sequencing and bioinformatic analysis to determine the genomic surroundings and syntenic chromosomal conservation of the genomic region contained in each BAC clone. The mFISH showed that the groups of genes hmgb2-trim25-irf5-b2m; tlr3-lysg; tnfα-tap1, and il10-mx-trim16 were co-localized on the same chromosomes. Synteny results suggested that the studied BACs are placed in a smaller number of chromosomes in S. senegalensis that in other species. Phylogenetic analyses suggested that the evolutionary rate of immune system genes studied is similar among the taxa studied, given that the clustering obtained was in accordance with the accepted phylogenetic relationships among these species. This study contributes to a better understanding of the structure and function of the immune system of the Senegalese sole, which is essential for the development of new technologies and products to improve fish health and productivity.